INTERNET BANKING, PROCEDURE FOR USING ONLINE FUNDS IN UZBEKISTAN - Karimova Shirin Zoxid qizi; Rustamova Ziyoda Anvar qizi; Madyarova Muxlisa Abdulla qizi (Modern American Journals, 2025)
This research focuses on the procedures for using internet banking and online payments in Uzbekistan. Nowadays, people prioritize convenience and speed when using banking services. Internet banking meets these needs by allowing users to manage accounts remotely, make payments, and access credit. In addition, e-wallets and mobile payment systems are becoming increasingly widespread. The study highlights the regulations governing payment systems in Uzbekistan, security issues, and the development of digital financial services.
Keywords: Internet banking, online payments, digital finance, e-wallet, mobile payment systems, banking services, Uzbekistan's financial system, digital security, payment system regulation, remote banking services.